A Standard Set of Outcome Measures for the Comprehensive Appraisal of Cleft Care. (September 2017) - Allori, Alexander C.; Kelley, Thomas; Meara, John G.; Albert, Asteria; Bonanthaya, Krishnamurthy; Chapman, Kathy; Cunningham, Michael; Daskalogiannakis, John; De Gier, Henriette; Heggie, Andrew A.; Hernandez, Cristina; Jackson, Oksana; et al.
Care of the patient with cleft lip and/or palate remains complex. Prior attempts at aggregating data to study the effectiveness of specific interventions or overall treatment protocols have been hindered by a lack of data standards. There exists a critical need to better define the outcomes- particularly those that matter most to patients and their families-and to standardize the methods by which these outcomes will be measured. This report summarizes the recommendations of an international, multidisciplinary working group with regard to which outcomes a typical cleft team could track, how those outcomes could be measured and recorded, and what strategies may be employed to sustainably implement a system for prospective data collection. It is only by agreeing on a common, standard set of outcome measures for the comprehensive appraisal of cleft care that intercenter comparisons can become possible. This is important for quality-improvement endeavors, comparative effectiveness research, and value-based health-care reform.